Yttrium Complexes of Arsine, Arsenide, and Arsinidene Ligands1. (5th February 2015) - Pugh, Thomas; Kerridge, Andrew; Layfield, Richard A.
Abstract: Deprotonation of the yttrium–arsine complex [Cp′3 YAs(H)2 Mes] (1 ) (Cp′=η 5 ‐C5 H4 Me, Mes=mesityl) by n BuLi produces the μ‐arsenide complex [Cp′2 Y[μ‐As(H)Mes]3 ] (2 ). Deprotonation of the AsH bonds in2 by n BuLi produces [Li(thf)4 ]2 [Cp′2 Y(μ3 ‐AsMes)3 Li], [Li(thf)4 ]2 [3 ], in which the dianion3 contains the first example of an arsinidene ligand in rare‐earth metal chemistry. The molecular structures of the arsine, arsenide, and arsinidene complexes are described, and the yttrium–arsenic bonding is analyzed by density functional theory.